A generalization of the AOR iteration method for solving absolute value equations - Cui-Xia Li (Electronic Research Archive, 2022)
In this paper, based on the accelerated over relaxation (AOR) iteration method, a generalization of the AOR iteration method is presented to solve the absolute value equations (AVE), which is called the GAOR method. The convergence conditions of the GAOR method are obtained. Numerical experiments are presented in order to verify the feasibility of the GAOR method.